2014
DOI: 10.1111/jrh.12071
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Park Environments and Park Use in Southern US Communities

Abstract: Purpose To document park use and park and neighborhood environment characteristics in rural communities, and to examine the relationship between park characteristics and park use. Methods The System for Observing Play and Recreation in Communities measured use in 42 target areas across 6 community parks in May 2010 and October 2010. Direct observation instruments were used to assess park and neighborhood environment characteristics. Logistic regression was used to determine the relationship between the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 50 publications
6
27
0
3
Order By: Relevance
“…A wide range of criteria were used for selecting parks, including prior or current participation in a research or grant initiative (Banda et al, 2014; Reed et al, 2012), availability of programming activities (Hino et al, 2010; Shores and West, 2008a), having dog-related park policies (McCormack et al, 2014; Temple et al, 2011), or whether the park offered a variety of amenities (Kaczynski et al, 2011; Muftuler et al, 2011), had a recreation center (Cohen et al, 2012), had at least one full-time staff (Cohen et al, 2012), or was designated for improvements (McKenzie et al, 2006). Some studies allowed the city park and recreation staff to choose the parks (Reed et al, 2008, 2012), while one study chose parks based on popular use by adult users (Pleson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A wide range of criteria were used for selecting parks, including prior or current participation in a research or grant initiative (Banda et al, 2014; Reed et al, 2012), availability of programming activities (Hino et al, 2010; Shores and West, 2008a), having dog-related park policies (McCormack et al, 2014; Temple et al, 2011), or whether the park offered a variety of amenities (Kaczynski et al, 2011; Muftuler et al, 2011), had a recreation center (Cohen et al, 2012), had at least one full-time staff (Cohen et al, 2012), or was designated for improvements (McKenzie et al, 2006). Some studies allowed the city park and recreation staff to choose the parks (Reed et al, 2008, 2012), while one study chose parks based on popular use by adult users (Pleson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies observed parks once during one season, with other studies observing multiple times across two (Banda et al, 2014; Cohen et al, 2011; Reed et al, 2012; Temple et al, 2011), three (Cohen et al, 2013), or all four seasons (Roemmich and Johnson, 2014). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Distance from origin (e.g., home) to public open space is still commonly measured using the straight line (Euclidean) distance (e.g., Banda et al, 2014). However, street network distance better represents the true relevant spatial distance (Apparicio et al, 2008;Zhang et al, 2011).…”
Section: Distance To Public Open Spacementioning
confidence: 99%